Extracts from the brains of hibernating and alert ground squirrels: effects on cells in culture. - Amorese, D A (1982)
Aqueous extracts were prepared from pulverized, acetone-dehydrated brains of hibernating and alert ground squirrels. Addition of these extracts to Chinese hamster ovary cells in suspension culture resulted in a decrease in the amount of [3H]thymidine incorporated into acid-precipitable material without affecting the transport or phosphorylation of the nucleoside. The inhibition was time- and dose-dependent and full recovery occurred about 2 hr after exposure of the cells to the active extract. The active factor is readily oxidized during storage at -70 degrees C but full activity can be restored by treatment with 2-mercaptoethanol. The peptide nature of the active material is indicated by its susceptibility to proteases and by loss of activity after alkylation. Fasted or cold-acclimated rats also develop increased levels of active substance in their brains; however, brains of hibernating squirrels contain 10- to 50-fold more of the active substance than brains from either alert squirrels or rats. A time-dependent increase in activity of extracts from hibernating brain incubated with a homogenate from alert brain suggests that the peptide is activated or generated in the mixture.